2012
DOI: 10.1007/s15010-012-0300-3
|View full text |Cite
|
Sign up to set email alerts
|

Experience with daptomycin daily dosing in ICU patients undergoing continuous renal replacement therapy

Abstract: In critically ill patients undergoing CRRT, daptomycin exposure with once-daily dosing was similar to ICU patients with normal renal function, but lower compared to healthy volunteers. Our data suggest that daptomycin once-daily dosing is appropriate in patients undergoing CRRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Preiswerk et al . showed that daptomycin exposure in critically ill patients undergoing CRRT after once‐daily dosing was similar to that in ICU patients with normal renal function. In the study by Rudiger et al .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Preiswerk et al . showed that daptomycin exposure in critically ill patients undergoing CRRT after once‐daily dosing was similar to that in ICU patients with normal renal function. In the study by Rudiger et al .…”
Section: Discussionmentioning
confidence: 86%
“…Overall, our results are largely consistent with those from Preiswerk et al . and Rudiger et al . , who also concluded that daily‐dosing regimens with daptomycin are more appropriate than dosing every second day in CRRT patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on a CRRT model with bovine plasma showing comparable clearance when compared with normal renal clearance [7], we settled for a once daily regimen at our intensive care units at the time. We recently published a retrospective chart analysis of 7 critically ill patients with routinely measured trough and in some cases additional peak concentrations [8]. All of the patients - although undergoing CRRT and receiving daptomycin doses above 6 mg/kg/day once daily in some cases - had daptomycin concentrations below those found in healthy volunteers at the equivalent dose [9,10].…”
Section: Introductionmentioning
confidence: 99%